Bragg spectroscopy of quantum gases: Exploring physics in one dimension - Fabbri, Nicole (Premio Tesi di Dottorato, 2012)
This thesis has been aimed at investigating the dynamical properties of one-dimensional gaseous nanowires, realized by trapping ultracold gases in laser-light lattice structures. The project was carried out at the European laboratory LENS in Florence, also with international collaborations. In recent years, one-dimensional systems have attracted great interest in different fields of physics, material science and chemistry, owing to their peculiar features: In this work, probing the response of the system to inelastic light-scattering experiments - Bragg spectroscopy - has allowed to explore the dynamics and the correlations inside these structures and the quantum phase-transition from superfluid to insulator, occurring due to inter-particle interactions.